2021
DOI: 10.1016/j.surfcoat.2021.127513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al content on the hardness and thermal stability study of AlTiN and AlTiBN coatings deposited by HiPIMS

Abstract: The microstructure, mechanical properties and thermal stability of Al x Ti 1− x N and Al 1 Ti 1-x BN coatings grown by reactive high-power impulse magnetron sputtering (HiPIMS) have been analyzed as a function of Al/(Al + Ti) ratio (x) between 0.5 and 0.8. The coatings were predominantly formed by a face-centered cubic Ti(Al)N crystalline phase, both with and without B, even for x ratios as high as 0.6, which is higher than the ratio typically encountered for Al x Ti 1− x N coatings deposited by reactive magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…In the XRD pattern of the as-deposited coating, peaks (111) and (002) corresponding to cubic (Ti,Al)N were identified ( Figure 7 a). The peaks were also found in previous studies [ 21 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], sometimes with slightly shifted 2θ values. This shift is caused by substitution of Ti by Al, and possibly Si, and also due to the effects of crystallite size and internal stresses [ 30 ].…”
Section: Resultssupporting
confidence: 84%
“…In the XRD pattern of the as-deposited coating, peaks (111) and (002) corresponding to cubic (Ti,Al)N were identified ( Figure 7 a). The peaks were also found in previous studies [ 21 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], sometimes with slightly shifted 2θ values. This shift is caused by substitution of Ti by Al, and possibly Si, and also due to the effects of crystallite size and internal stresses [ 30 ].…”
Section: Resultssupporting
confidence: 84%
“…Therefore, hardness reduction didn't occur due to the phase transformation. Mendez et al 37 found that the hardness of AlTiN coatings with high Al concentration is greater than that of AlTiN coatings with low Al content.…”
Section: Resultsmentioning
confidence: 99%
“…Although the hardness values of coatings B, C, and D were found to be consistent with the literature, coating A's hardness was found to be significantly low. [35][36][37] The Daimler-Benz Rockwell-C adhesion test was used to determine the degree of coating-substrate adhesion. 38,39 The indentation trace was inspected after the adhesion test to identify fractures or delamination surrounding the trace and ranked between HF-1 and HF-6 where the HF-1 to HF-3 accepted adhesion levels for the coatings (see Figure 3).…”
Section: Characterization Results Of Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TiAlN deposition rate is calculated to be approximately 2.5 µm/h. Based on the previous results in the same batch coater, it is assumed that most of the film material would be deposited when the substrate faces the operating magnetron (in this case, the TiAl DCMS), thus, a TiAlN nano-layer of a maximum thickness of 3.3 nm would be deposited on each pass (approximately 8 ML) [12]. Still, it is well known for batch coaters that a certain degree of depositing material reaches the substrate in off-angle positions or at positions very distant from the ignited magnetron, so further investigations to identify the accurate nano-layer thickness should be carried out by, for example, transmission electron microscopy.…”
Section: Methodsmentioning
confidence: 99%